Interactive Learning Multimedia in Supporting Personalized Learning Grade V Primary School - Lovandri Dwanda Putra; Try Syukrianto S (Universitas Pendidikan Ganesha, 2023)
The absence of interactive media and media development in an area shows that adaptation to technology has yet to be maximized. The research aimed to produce interactive multimedia material on human blood circulation for grade V SD and determine its quality and feasibility by conducting validation trials on experts, teachers, and students. This research method is R&D (Research and Development) with the ADDIE model. The subjects in this study were fifth-grade elementary school students. Data collection methods are assessment sheets and documentation. Data collection instrument using a questionnaire. Data analysis techniques are quantitative data analysis and qualitative descriptive data analysis. The results of the research are in the form of interactive multimedia based on storylines of articulation of human blood circulation in science subjects for class V SD which can be used by students with a score of 92.5% from material experts; media experts 86.66%; learning experts 88.88%; linguists 74.26%; teacher assessment 98.88%; Penialain students 93.40%. The scores of each expert, teacher, and student assessment were then searched for the average value and obtained a percentage value of 89.096% with the